Evaluation of the Quasi‐Biennial Oscillation in global climate models for the SPARC QBO‐initiative. (14th March 2020) - Bushell, A. C.; Anstey, J. A.; Butchart, N.; Kawatani, Y.; Osprey, S. M.; Richter, J. H.; Serva, F.; Braesicke, P.; Cagnazzo, C.; Chen, C.‐C.; Chun, H.‐Y.; Garcia, R. R.; et al.
Abstract: Quasi‐biennial oscillations (QBOs) in thirteen atmospheric general circulation models forced with both observed and annually repeating sea surface temperatures (SSTs) are evaluated. In most models the QBO period is close to, but shorter than, the observed period of 28 months. Amplitudes are within ±20 % of the observed QBO amplitude at 10 hPa, but typically about half of that observed at lower altitudes (50 and 70 hPa). For almost all models, the oscillation's amplitude profile shows an overall upward shift compared to reanalysis and its meridional extent is too narrow. Asymmetry in the duration of eastward and westward phases is reasonably well captured, though not all models replicate the observed slowing of the descending westward shear. Westward phases are generally too weak, and most models have an eastward time mean wind bias throughout the depth of the QBO. The intercycle period variability is realistic and in some models is enhanced in the experiment with observed SSTs compared to the experiment with repeated annual cycle SSTs. Mean periods are also sensitive to this difference between SSTs, but only when parametrized non‐orographic gravity wave (NOGW) sources are coupled to tropospheric parameters and not prescribed with a fixed value. Overall, however, modelled QBOs are very similar whether or not the prescribed SSTs vary interannually. A portrait of the overall ensemble performance is provided by a normalized grading of QBO metrics. To simulate a QBO, all but one model used parametrized NOGWs, which provided the majority of the total wave forcing at altitudes above 70 hPa in most models. Hence the representation of NOGWs either explicitly or through parametrization is still a major uncertainty underlying QBO simulation in these present‐day experiments. Abstract : Quasi‐biennial oscillations (QBOs) in thirteen atmospheric general circulation models forced with both observed (orange) and annually repeating (grey) sea surface temperatures (SSTs) are evaluated over a range of metrics and compared against reanalysis (blue‐green). Mean periods are sensitive to this difference between SSTs, but only when parametrized non‐orographic gravity wave sources are coupled to tropospheric parameters (60LCAM5 and right there of) and not prescribed with fixed values. Overall, however, modelled QBOs are very similar whether or not the prescribed SSTs vary interannually.